CALPHAD simulation of the Mg–(Mn, Zr)–Fe system and experimental comparison with as-cast alloy microstructures as relevant to impurity driven corrosion of Mg-alloys - Gandel, D.S.; Easton, M.A.; Gibson, M.A.; Birbilis, N. (Materials chemistry and physics, 2014)
Four Mg alloys with variations in the ratio of Mn, Zr and Fe additions were cast and their microstructures analysed via electron microscopy. Thermodynamic calculations of the expected phases using PANDAT were evaluated with actual as-cast microstructures. Some of the as-cast alloys did appear to form phases similar to those anticipated from the PANDAT calculations. Furthermore, there was a new Mn–Fe particle interaction observed that was not predicted, but which is posited to be responsible for the increase in corrosion resistance among Mn containing Mg alloys with Fe impurities. The experimental work herein has been shown to be invaluable in the understanding of this practically important system with sparingly soluble Fe and its potential influence on the corrosion of Mg alloys. •Alloy microstructure of the Mg-(Mn,Zr, Fe) system was analysed and reported.•CALPHAD analysis was used in conjunction with traditional SEM analysis techniques in this study.•A proposed Mn–Fe interaction within Mg has been observed for the first time.•Experimental validation of calculated phases is required to understand the effect of Mn and Zr on Mg .